Carbon Nanodots as Complexing Agent in the Formation of Lead(II) Sulfide Thin Films via Direct Deposition of Lead(II) Sulfide Powder - Ariswan Ariswan; Bian Itsna Ashfa Al Ashfiya; Anisha Nurcahyati; Wipsar Sunu Brams Dwandaru (Directorate for Research and Community Services (LPPM) ITB, 2023)
This study reveals for the first time the formation of lead(II) sulfide (PbS) thin films via direct deposition of PbS powder using carbon nanodots (Cdots) as a complexing agent. The chemical bath deposition (CBD) technique was utilized and the Cdots’ mass was varied, i.e., (in g) 3, 5, 7, and 9. The Cdots were prepared from the waste of a rice noodle production home industry via the low-temperature carbonization method. The Cdots were characterized using UV-Vis spectrophotometry, showing absorption peaks at 275 nm and 325 nm; PL, showing an emission peak at 500 nm with cyan luminescence; XRD, showing several peaks, indicating an incomplete carbonization process; FTIR, indicating the existence of C=C, C-H, C-O, and O-H functional groups; HRTEM, revealing the sizes of the Cdots in the range of 2 nm to 6 nm; and SEM, showing a smooth morphology of the Cdots’ surface. The thin films obtained were smooth with higher XRD peaks and better material distribution compared to pure PbS thin film. The band gap measurement indicated that the increase of the PbS band gap was caused by the increase of the Cdots’ mass. Hence, the thin films’ band gap may be tuned using the Cdots’ mass.